Diet, nutrition and femoral robusticity of hunter‐gatherers in southern Patagonia: experiences and perspectives - Suby, Jorge Alejandro (2009)
Dietary reconstructions through stable isotope studies are one of the most prominent tools for analysing the impact of nutritional and subsistence strategy transitions in the health of past human populations. In the last few years, some palaeopathological studies have been developed related to dietary models proposed for southern Patagonia. In the present work we study the femoral diaphyseal robusticity as an indicator of physical activity and health of a sample of hunter-gatherer individuals from southern Patagonia in relation to their diet,recorded by means of stable isotope values. We discuss the relationship between nutrition and the characteristics of bone structure, as well as the possible impact of pathologies as a source of variability in stable isotope values.